A New Species of Waginella (Crustacea: Thecostraca: Ascothoracida) Parasitic on a Stalked Crinoid From Tasman Sea, With Notes on Morphology of Related Genera - Kolbasov, Gregory A.; Savchenko, Alexandra S.; Newman, William A.; Chan, Benny K. K. (Frontiers in Marine Science, 2021)
A new ectoparasitic ascothoracidan species has been discovered off northern Tasman Sea at a depth of 520 m. Single female, described herein as Waginella ebonita Kolbasov and Newman sp. nov. in the family Synagogidae Gruvel, 1905, was collected on the column of crinoid Metacrinus sp. This is the first study of a new form of Waginella to be based on the extensive use of both light and scanning electron microscopy to document the fine-scale external morphology. We studied the external morphology of other two species of Waginella, W. cf. axotremata and W. sandersi utilizing SEM and compared fine structures of all congeners. The genus Waginella represents a monophyletic taxon including at least 4 species having similar and unique morphology even on the ultrastructural level. Two species, W. cf. axotremata and W. cf. metacrinicola may represent at least two complexes of species. The morphology of an attachment apparatus in all species of Waginella suggests that they remain attached to the host for a considerable period of time. The lattice organs of Waginella have a unique structure distinguishing from all Thecostraca. Waginella ebonita sp. nov. is the second species of this genus known to harbor hyperparasitic cryptoniscid isopods representing parasitic castrators.